Analisis Rasio Keuangan Untuk Memprediksi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Vira Yunika; Maizul Rahmizal (JURNAL PUNDI, 2022)
This study aims to determine the effect of financial ratios on financial distress. This type of research is quantitative research. The sample consists of 12 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 using purposive sampling. The data analysis used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results show that the profitability ratios, liquidity ratios, leverage ratios and activity ratios have a positive and significant effect on financial distress in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019